Effect of oil price volatility on the trade balance in sub-Saharan Africa - Forson, Priscilla; Dramani, John Bosco; Frimpong, Prince Boakye; Arthur, Eric; Sulemana, Mahawiya (OPEC Energy Review, 2024)
This is an article published in OPEC Energy Review, September 2022